Pendidikan Kewarganegaraan dalam Mengembangkan Civic Tech Skills untuk Partisipasi Politik Digital: Citizenship Education in Developing Civic Tech Skills for Digital Political Participation - Ahmad Muhamad Mustain Nasoha; Shafira Aulia Putri; Meifta Dian Safitri (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The advancement of digital technology has brought significant changes to the patterns of political participation in society. In this context, Civic Education (PKn) plays an essential role in fostering civic technology skills (Civic Tech Skills) to enable citizens to participate actively and responsibly in digital spaces. This study employs a qualitative approach by analyzing various literature sources and relevant social phenomena. The findings show that Civic Education not only provides political knowledge but also nurtures critical thinking, democratic values, and practical skills for digital interaction, particularly through social media. By integrating civic values with technological utilization, this education helps the younger generation express their aspirations, engage in political discussions, and contribute to building an inclusive and adaptive society in response to contemporary developments. Therefore, Civic Education serves as a vital means of shaping digital citizens who are intelligent, ethical, and ready to face the challenges of democracy in the digital era.